Red Eagle's Children : Weatherford vs. Weatherford et al. - Paredes, J. Anthony (James Anthony), 1939-; Knight, Judith (Book collections on Project MUSE., 2012)
This book presents the legal proceedings in an inheritance dispute that serves as an unexpected window into the intersection of two cultural and legal systems: Creek Indian and Euro-American. Case 1299: Weatherford vs. Weatherford et al. appeared in the Chancery Court of Mobile in 1846 when William "Red Eagle" Weatherford's son by the Indian woman Supalamy sued his half siblings (fathered by Weatherford with two other Creek women, Polly Moniac and Mary Stiggins) for a greater share of Weatherford's estate. While the court recognized William Jr. as the son of William Sr., he nevertheless lost his petition for inheritance due to the lack of legal evidence concerning the marriage of his biological mother to William Sr. The case, which went to the Alabama Supreme Court in 1851, provides a record of an attempt to interrelate and, perhaps, manipulate differences in cultures as they played out within the ritualized, arcane world of antebellum Alabama jurisprudence. This book shows that its more enduring value lies in being a source for historical ethnography - that is, for anthropological analyses of cultural dynamics of the past events that complement the narratives of professional historians.